Benign Anorectal Disorder Management in Low-Resource Settings - Oliveira, Lucia; Galindo, Gonzalo Federico Hagerman Ruiz; Silva-Velazco, Jorge Daniel (Clinics in Colon and Rectal Surgery, 2022)
There are many benign anorectal disorders, which can make patients seek care. In low-resource settings, the incidence of those pathologies is not different from the industrialized and western world. However, an interesting difference colorectal surgeons and gastroenterologists can face is the fact that many patients do not seek help or are not aware and have little opportunities to be helped. Latin America population is estimated to be around 8% of the world population, with Brazil having the largest percentage. Infectious diseases, which were previously under control or were steadily declining, have emerged. For example, we have seen resurgence of dengue, malaria, and syphilis in pregnancy, as well as other sexually transmitted diseases that can affect the anorectal region. In this article, we will address the most common benign anorectal disorders.
Keywords: anorectal; benign; anal; abscess; fistula; incontinence